2021
DOI: 10.1101/2021.05.21.445205
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Noninvasive genetic surveys before and after a megafire detect displacement of migratory mule deer

Abstract: Due to climate change and past logging and fire suppression, the western US are experiencing increasingly large and frequent wildfires. Understanding how wildlife respond to these mega-fires is becoming increasingly relevant to protect and manage these populations. However, the lack of predictability inherent in such events makes studies difficult to plan. We took advantage of a large high-severity wildfire that burned adjacent to an ongoing study of mule deer (Odocoileus hemionus) on their summer range upslo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…These observations qualitatively mirror those observed in previous studies, but differ somewhat in the timing. A study of mule deer in the Sierra Nevada of California that was interrupted by another large fire (King Fire in 2014) found that abundance of deer increased within the first 2 months on unburned sites adjacent to the fire, but had declined by the following year to pre‐fire levels (Brazeal et al., 2021). This observation could have reflected the timing of that fire relative to the migratory status of that population; shortly after the fire occurred on summer range, deer migrated to their wintering grounds before returning the following summer, whereas in the present study, nonmigratory deer could have remained continuously in the same habitats to which they escaped the fire.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These observations qualitatively mirror those observed in previous studies, but differ somewhat in the timing. A study of mule deer in the Sierra Nevada of California that was interrupted by another large fire (King Fire in 2014) found that abundance of deer increased within the first 2 months on unburned sites adjacent to the fire, but had declined by the following year to pre‐fire levels (Brazeal et al., 2021). This observation could have reflected the timing of that fire relative to the migratory status of that population; shortly after the fire occurred on summer range, deer migrated to their wintering grounds before returning the following summer, whereas in the present study, nonmigratory deer could have remained continuously in the same habitats to which they escaped the fire.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, studies of deer responses to wildfire have primarily documented use of, but not dietary intake in, burned versus unburned sites after a wildfire (Brazeal et al., 2021; Cave et al., 2021). In general, deer tend to move out of burned sites to unburned sites immediately after fires and return to burned areas after varying timespans, depending on vegetation regeneration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the frequency, size, and severity of wildfires have increased recently. Wildfires have been shown to displace migratory species such as mule deer (Brazeal, Sollmann & Sacks, 2021) and even bird species (tule geese, Anser albifrons elgasi), and can disrupt migratory behaviour, and increase both energetic demands and mortality risk (Overton et al, 2022). On the other hand, fire suppression can result in changes to habitat structure such as increased density of tree stands and understory (Gilliam & Platt, 1999).…”
Section: (6) Human Intrusions and Disturbancementioning
confidence: 99%